Biosynthetic Machinery of 6‐Hydroxymellein Derivatives Leading to Cyclohelminthols and Palmaenones. (18th October 2019) - Ugai, Takahiro; Minami, Atsushi; Tanaka, Shizuya; Ozaki, Taro; Liu, Chengwei; Shigemori, Hideyuki; Hashimoto, Masaru; Oikawa, Hideaki
Abstract: Oxygenated cyclopentene systems are unique structural motifs found in fungal polyketides such as terrein, cyclohelminthols, and palmaenones. Here we report the identification of the biosynthetic gene clusters for cyclohelminthols and palmaenones and the functional characterization of the polyketide synthases and halogenases involved in the construction of 6‐hydroxymellein derivatives. Heterologous expression in Aspergillus oryzae demonstrated that 6‐hydroxymellein is a common biosynthetic intermediate and that chlorination occurs in the early stages of its products' biosynthesis. This was further confirmed by in vitro enzymatic reactions conducted in the presence of recombinant proteins. Plausible means of biogenesis of fungal polyketides from 6‐hydroxymellein derivatives, additionally supported by the reported labeling patterns of terrein and structurally related fungal polyketides, are also discussed. This study sets the stage for elucidation of the biosynthetic machinery of fungal polyketides of this type. Abstract : Common biogenesis of fungal polyketides via 6‐hydroxymellein : Biosynthetic pathways starting from 6‐hydroxymellein and its chlorinated derivatives were elucidated by pathway refactoring in A. oryzae and through in vitro enzymatic reactions. A polyketide synthase (ChmAB) and flavin‐dependent halogenases (ChmKN and PloK) were functionally characterized.